Potensi Bahaya pada Ujung Runway 24 Bandar Udara: Sebuah Implementasi Manajemen Resiko - Rahmat Riyadi; Oke Hendra; Rini Sadiatmi; Wildan Nugraha; Direstu Amalia (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2021)
This research aims to analyzethe hazards that exist at the end of runway 24 at Juwata Tarakan Airport.Then how to reduce the risks that exist in the area.The method that used for this research is the qualitative method. the data collection has been gained by observation, attendingdirectly into the field to analyze the hazards that exist at the end of the runway 24, depth interview with key informant, and document study on the accident historical data of the airport, respectively. Furthermore, the data was analyzed by risk management standardizationof AS/NZS 4360. Theresult show thatthe runwaypositionis near withthe road so it couldendanger motorists who pass on the highway. Moreover, therisk of jet blastbursts might cause an accident. After this research was carried out, a solution was obtained to reduce the existing risks by implementing a system of opening and closing traffic on the highway. In addition, it can also be done by diverting the flow of traffic on the highway.